Question of Hungary. Sixteenth Session, Agenda Item 89, 1087th Plenary Meeting - Héderváry, Claire de (1961)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly New resolution on Hungary was proposed. A4996 report by Leslie Munro shows that what is going on in Hungary is still a matter of anxiety: the persecutions and repression are continuing. The new resolution calls deplorable "the continued disregard by the USSR and the present Hungarian regime of the General Assembly resolutions concerning the situation in Hungary". The new resolution is adopted by 49 to 17 votes with 32 abstentions.